The contours of employee voice in SMEs: the importance of context. (18th September 2015) - Gilman, Mark; Raby, Simon; Pyman, Amanda
Abstract : This article develops a context‐sensitive approach to analyse how and why voice operates in small‐ to medium‐sized enterprises (SMEs), an area that remains under‐theorised and under‐researched. By building on a priori frameworks with proven ability to unpack complexity and take account of the wider context of SMEs, this article explores how resources (human and social capital) and constraints (product market, labour market and strategic orientation) interact to shape voice practices. The article finds significant differences between 'reported' compared with 'actual' practices in situ, and identifies different types of firms ('strategic market regulation', 'strategic market‐led' and 'non‐strategic market‐led') along with the factors that influence the form and practice of voice. Overall, the article argues that researchers should further pursue research that appreciates the layered nature of ontology and the role played by firm context to explain complex organisational phenomena, if we are to advance our understanding of voice practices in SMEs and beyond.